The Development of Testlet Assessment Instrument Model Integrated with E-ujian Website to Measure the Higher-Order Thinking Skills - Dwijayanti, Kartika Dyah Permata Mega; Savitri, Erna Noor (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
This research and development research aimed to determine the feasibility and characteristics of the Testlet model assessment instrument integrated with the E-ujian website in measuring the Higher-order Thinking Skills (HOTS) of junior high school students. The researchers employed the 4D development model (define, design, develop and disseminate). However, the researchers conduct the development up to the develop stage. The research was conducted at a junior high school with 42 students as respondents. The researchers collected the data through test techniques, questionnaires, interviews, observation, and documentation. This development research utilized the descriptive-quantitative data analysis method through characteristic tests, teacher and students’ questionnaire responses analysis, and analysis of students' HOTS profiles. The students’ HOTS profiles based on the assessment instrument were divided into 53 percent of students in the poor HOTS category, 31 percent of students in the low HOTS category, and 16 percent of students in the high HOTS category. Concluded that the assessment instrument developed was very feasible, with a percentage of 94 percent. The assessment instrument developed had the characteristics of valid, reliable, discriminatory, disproportionate, relevant, representative, impractical, and specific. The Testlet model assessment instrument development can be used as an alternative for the distance learning assessment during the Covid-19 pandemic.